Lessons in scientific computing : numerical mathematics, computer technology, and scientific discovery - Schorghofer, Norbert (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
"This new book is a modernized, exceptionally broad and intentionally compact introduction to scientific computing. It takes a broad and interdisciplinary approach; numerical methods, computer technology and their interconnections are treated with the goal of facilitating scientific research. Each chapter provides an insightful lesson, and viewpoints from several subject areas are often compounded within a single chapter. The material is written with an eye on usefulness, longevity, and breadth"--
Analytical & numerical solutions -- A few concepts from numerical analysis -- Roundoff & number representation -- Programming languages & tools -- Sample problems; building conclusions -- Approximation theory -- Other common computational methods -- Performance basics & computer architectures -- High-performance & parallel computing -- The operation count; numerical linear algebra -- Random numbers & stochastic methods -- Algorithms, data structures, and complexity -- Data -- Building programs for computation and data analysis -- A crash course on partial differential equations -- Reformulated problems.
Includes bibliographical references and index.
CSE
Parama
Keywords: Science -- Mathematics -- Data processing; Numerical analysis -- Data processing; Computer science